Problems in Small Mammal Radioecology - Baryakhtar, V G; Bondarkov, MD; Gaschak, S P; Goryanaya, JA; Maximenko, A M; Liabik, V V; Chesser, R K; Baker, R G (Environmental science and pollution research international, 2003)
Small mammals, particularly mouse rodents and shrews, have for a long time been objects of great interest to radioecologists. First, they are convenient and popular subjects for pilot research, because they have high reproductive rates and require simple conditions for laboratory housing. In addition, these wild rodents have extensively studied laboratory prototypes, which may also serve as test models for radiation effects/consequences research, and the data from these studies may also be extrapolated to radiation effects in humans. Their permanently inhabiting an ecosystem in areas highly contaminated with radioactive fallout (namely, on the soil"s surface and in topsoil), as well as their small body sizes, stipulate considerably greater radiation vulnerability for these small mammals relative to that of larger mammals. By eating environmental objects, these mouse rodents and shrews accumulate considerable amounts of radioactive matter, thus being both temporary repositories in the ecosystem, and the source of radionuclide intake for other animals. This group of mammals is the most numerous and constitutes the greatest biomass within the mammalian species. These facts have played an important role in the research on this group. Their restricted seizing from biocenoses in scientific study does not undermine the reproductive potential of the population and ecosystem as a whole. Moreover, because many of these species are potential pests in agriculture and forestry, and carriers of dangerous diseases to human and agricultural animals, the utility of research on these small mammals living in radioactively contaminated areas is increased. During last 30 to 40 years, the radioecological issues of this group have been studied thoroughly. Mouse rodents were also used as test-models during the study of radioactive isotopes" biological effects, the consequences of nuclear tests in the atmosphere, and the consequences of technogenic radiation contamination of the environment. However, the consequences of the Chernobyl accident, which included (1) multicomponent compositions with complex levels, (2) vari- ous territorial distributions of radioactive fallout, (3) the regional features of biocenoses (absorptive soils), and (4) a wide variety of soil-vegetable and hydrological conditions, all required new efforts in this direction. In addition, many issues and problems of smali-mammal radioecology of theoretical value remained poorly understood. The review following summarizes available information produced by scientists from Ukraine, Russia, and Belarus while studying radioecological and radiobiological consequences during the period from 1986 to 1995 following the Chernobyl accident. Data derived from 1996 to 2002 are based on the results of our own research and that performed jointly with United Kingdom and United States scientists within the Chernobyl Zone. When the methodical approach and the quality of the received data differ, these differences are noted.